1996
DOI: 10.2135/cropsci1996.0011183x003600030040x
|View full text |Cite
|
Sign up to set email alerts
|

Additional Sources of Resistance to Tan Spot of Wheat

Abstract: Tan spot, a foliar disease of wheat (Triticum aestivum L. em Thell) and durum (T. turgidum var. durum L.) caused by Pyrenophora triticirepentis (Died.) Drechs., reduces yield in susceptible cultivars by 3 to 50%. Additional sources for resistance to tan spot were sought in germplasm consisting of a collection of spring wheats previously screened for reaction to spot blotch [Cochliobolus sativus (Ito & Kurib.) Drech. ex Dastur] in Brazil, wheat cultivars recommended for cultivation in the state of Paraná, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 0 publications
0
30
0
2
Order By: Relevance
“…However, resistance occurs at different levels in many spring and winter types especially in Brazilian spring wheats. High levels of resistance in bread wheat and synthetic wheat have been observed by other researchers (Tadesse et al 2006a, b;Riede et al 1996). In a recent evaluation of 126 adapted durum and hard red spring wheat cultivars and breeding lines from the Prairie region of North America, observed ten genotypes showing high level of resistance to multiple races of P. tritici-repentis and their toxins.…”
Section: Sources Of Resistancementioning
confidence: 61%
“…However, resistance occurs at different levels in many spring and winter types especially in Brazilian spring wheats. High levels of resistance in bread wheat and synthetic wheat have been observed by other researchers (Tadesse et al 2006a, b;Riede et al 1996). In a recent evaluation of 126 adapted durum and hard red spring wheat cultivars and breeding lines from the Prairie region of North America, observed ten genotypes showing high level of resistance to multiple races of P. tritici-repentis and their toxins.…”
Section: Sources Of Resistancementioning
confidence: 61%
“…are major foliar diseases of wheat in North America (Fernandez et al 1998;Gilbert and Woods 2001). Leaf spots on average cause yield losses of 10-15%, however, under conditions favorable for disease development, losses can be as high as 50% (King et al 1983;Riede et al 1996). Leaf spots also cause signiWcant losses in grain quality by grain shriveling, red smudge, and black point (Fernandez et al 1998;McKendry et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Cloning of the gene encoding Ptr ToxA demonstrated that toxin production is sufficient for the pathogenicity of P. triticirepentis on wheat (Ciuffetti et al 1997). However, it was observed that under growth chamber conditions, a Ptr ToxA insensitive line can be highly susceptible to P. tritici-repentis when inoculated with conidia of the necrosis-inducing only race (race 2) and a Ptr ToxA sensitive line can be resistant to conidial inoculation (Riede et al 1996). The inconsistency between Ptr ToxA sensitivity and susceptibility to conidial inoculation may suggest that other factors besides toxin sensitivity may be involved in the hostpathogen interaction.…”
mentioning
confidence: 99%